การออกแบบผังโรงงานและปรับปรุงกระบวนการผลิตประตูไม้บานเลื่อน: Plant Layout Design and Process Improvement in Wood Sliding Door Manufacture - Chantarasamai, Krit; Lasunon, On-Uma (Asian Health, Science and Technology Reports, 2017)
งานวิจัยนี้มีวัตถุประสงค์เพื่อนำเสนอแนวทางการออกแบบผังโรงงานและปรับปรุงกระบวนการผลิตประตูไม้บานเลื่อน โดยการประยุกต์ใช้หลักการของการวางผังโรงงานอย่างมีระบบและหลักการ ECRS (กำจัด รวม จัดลำดับใหม่ ทำให้ง่าย) ในการปรับปรุงกระบวนการผลิต เพื่อลดเวลาในการทำงาน เวลาในการเคลื่อนที่และเวลาในการผลิตรวมต่อชุดให้น้อยลง โดยขั้นตอนในการวิจัยจะเริ่มจากการบันทึกข้อมูลด้วยแผนภูมิกระบวนการผลิตและแผนภูมิการไหล แล้วทำการวิเคราะห์เพื่อหาสาเหตุของปัญหาที่เกิดขึ้นด้วยผังแสดงเหตุและผล จากนั้นทำการออกแบบผังโรงงานและปรับปรุงกระบวนการผลิต เพื่อทำการเปรียบเทียบเวลาทั้งหมดที่ใช้ในการผลิตประตูไม้บานเลื่อน โดยการใช้เทคนิคการจำลองสถานการณ์ด้วยโปรแกรมโปรโมเดล ผลจากการจำลองสถานการณ์ พบว่า สามารถลดเวลาในการทำงานโดยเฉลี่ยประมาณร้อยละ 7 จากเดิม 51.90 ชั่วโมง เหลือ 48.30 ชั่วโมง ลดเวลาเฉลี่ยในการเคลื่อนที่ประมาณร้อยละ 80 จากเดิม 43.30 นาที เหลือ 8.80 นาที และลดระยะเวลาในการผลิตรวมประมาณร้อยละ 8 จากเดิม 52.60 ชั่วโมงต่อชุด เหลือ 48.40 ชั่วโมงต่อชุด This research aimed to propose an appropriate plant layout design and improve sliding door manufacturing processes. Systematic Layout Planning (SLP) and principle of ECRS (Eliminate, Combine, Rearrange, and Simplify) were used to reduce operation, transportation and total production times per set. Firstly, production process chart and flow diagram were used to record current working method and production time. A cause and effect diagram was used to understand the problems. Then, a proposed plant layout design and improved manufacturing processes were developed. Total production times using current and proposed methods were simulated using the Promodel program. The results showed that average operation time was reduced by about 7% from 51.90 to 48.30 hours. Average transportation or moving time was decreased by about 80% from 43.30 to 8.80 minutes. Average production time was reduced by about 8% from 52.60 to 48.40 hours per set.